Codificação de Cadeia Eficientes para Compactação da Informação de Forma em Compressão de Vídeo Baseada em Objetos DOI: 10.14209/jcis.2003.18 - Carlos Acocella, Emilio; Alcaim, Abraham (Journal of Communication and Information Systems, 2015)
In applications of object-based video compression, one of the most efficient strategies for lossless coding of object shapes is the differential chain coder (DCC). In this paper, several modifications of a DCC are identified and analyzed with the purpose of improving its efficiency. The number of spatial prediction classes in a conditional DCC was increased. In addition, we explored in a more effective and integrated form, the spatial and temporal correlations between pixels of the object contour. As compared to the methods available in the literature, the modifications that provided the highest compaction of the shape information were incorporated to the three schemes proposed in this paper: the adaptive conditional DCC, the DCC conditioned to the current frame and the DCC conditioned to the previous frame. In all cases, we have also considered the effects of different choices for the table of the Huffman codes, over the final compression rate.